2016
DOI: 10.1074/jbc.m116.714568
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Domains of GlcNAc-1-phosphotransferase Mediate Recognition of Lysosomal Enzymes

Abstract: The Golgi enzyme UDP-GlcNAc:lysosomal enzyme N-acetylglucosamine-1-phosphotransferase (GlcNAc-1-phosphotransferase), an ␣ 2 ␤ 2 ␥ 2 hexamer, mediates the initial step in the addition of the mannose 6-phosphate targeting signal on newly synthesized lysosomal enzymes. This tag serves to direct the lysosomal enzymes to lysosomes. A key property of GlcNAc-1-phosphotransferase is its unique ability to distinguish the 60 or so lysosomal enzymes from the numerous nonlysosomal glycoproteins with identical Asn-linked g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
62
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 40 publications
(67 citation statements)
references
References 35 publications
4
62
0
Order By: Relevance
“…Proteolytic cleavage of this precursor at K928 to give rise to the α and β subunits is mediated by the Site-1 protease in the Golgi, and this process is essential for catalytic competency of the protein 8, 9. The α subunit contains two Notch modules and a DNA methyltransferase-associated protein (DMAP) interaction domain that mediate the specific recognition of protein determinants on the lysosomal enzyme substrates (Figure 1A) 12 . In addition, there are four so-called spacer domains in the α/β precursor whose functions are beginning to be elucidated.…”
Section: Resultsmentioning
confidence: 99%
“…Proteolytic cleavage of this precursor at K928 to give rise to the α and β subunits is mediated by the Site-1 protease in the Golgi, and this process is essential for catalytic competency of the protein 8, 9. The α subunit contains two Notch modules and a DNA methyltransferase-associated protein (DMAP) interaction domain that mediate the specific recognition of protein determinants on the lysosomal enzyme substrates (Figure 1A) 12 . In addition, there are four so-called spacer domains in the α/β precursor whose functions are beginning to be elucidated.…”
Section: Resultsmentioning
confidence: 99%
“…Since many MRH domains act as lectins that bind both M6P modified and non-modified high mannose oligosaccharides, its presence in the γ subunit suggests that it might facilitate subunit ability to bind the N-glycans of hydrolases, thereby modulating the αβ’s recognition capability (17). It was also suggested that the MRH domain binds glycans on the α subunit, but a recent study demonstrated that interaction between the αβ and γ subunits is MRH-independent (18). …”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, the lysosomes accumulate undegraded material. The α and β subunits of GlcNAc-1-phosphotransferase, encoded by the gene GNPTAB, harbor the catalytic site as well as domains that mediate the recognition of the acid hydrolases (DMAP and Notch repeats) (Kudo, et al, 2005; Qian, et al, 2013; Qian, et al, 2010; Qian, et al, 2015; van Meel, et al, 2016). Depending on the residual level of GlcNAc-1-phosphotransferase activity, mutations in GNPTAB either cause the very severe lysosomal storage disorder mucolipidosis (ML) II (MIM# 252500), or result in MLIII αβ (MIM# 252600), which has an attenuated phenotype (Kudo, et al, 2006).…”
mentioning
confidence: 99%
“…GNPTG -/- HeLa cells have greatly reduced levels of many lysosomal acid hydrolases compared to the parental HeLa cells and display a lysosomal storage phenotype (van Meel, et al, 2016). In these cells, transient transfection with WT γ resulted in a marked increase in the intracellular activities of a panel of lysosomal glycosidases 3 days after transfection, with the maximum increase set to 100% rescue.…”
mentioning
confidence: 99%
See 1 more Smart Citation